3D Differentiation of LUHMES Cell Line to Study Recovery and Delayed Neurotoxic Effects. Issue 1 (4th August 2017) - Harris, Georgina; Hogberg, Helena; Hartung, Thomas; Smirnova, Lena
Abstract: Current neurotoxicity testing and the study of molecular mechanisms in neurodegeneration in vitro usually focuses on acute exposures to compounds. 3D Lund human mesencephalic (LUHMES) cells allow long‐term treatment or pulse exposure in combination with compound washout to study delayed neurotoxic effects as well as recovery and neurodegeneration pathways. In this unit we describe 3D LUHMES culture and characterization. Characterization of the model involves immunocytochemistry, flow cytometry, and qPCR measurements. Studying the delayed effects of compounds is more relevant to human exposures and neurodegenerative diseases with a strong genetic or environmental component. Most assays for molecular endpoints have been developed for monolayer cell culture and therefore need to be adapted for 3D models. In this unit, we further describe toxicological assays for molecular endpoints such as ATP levels, mitochondrial viability, and neurite outgrowth, which have been adapted for use in 3D LUHMES cultures. © 2017 by John Wiley & Sons, Inc.